Grafted Human iPSC-Derived Neural Progenitor Cells Express Integrins and Extend Long-Distance Axons Within the Developing Corticospinal Tract - Forbes, Lindsey H.; Andrews, Melissa R. (Frontiers in Cellular Neuroscience, 2019)
After spinal cord injury (SCI), regeneration of adult motor axons such as axons in the corticospinal tract (CST) is severely limited. Alongside the inhibitory lesion environment, most neuronal subtypes in the mature central nervous system (CNS) are intrinsically unrepairable. With age, expression of growth-promoting proteins in neurons, such as integrins, declines. Integrin receptors allow communication between the extracellular matrix (ECM) and cell cytoskeleton and their expression in axons facilitates growth and guidance throughout the ECM. The α9β1 integrin heterodimer binds to tenascin-C (TN-C), an ECM glycoprotein expressed during development and after injury. In the mature CST however, expression of the α9 integrin subunit is downregulated, adding to the intrinsic inability of axons to regenerate. Our previous work has shown the α9 integrin subunit is not trafficked within axons of mature CST or rubrospinal tracts (RSTs). Thus, here we have utilized human induced pluripotent stem cell (iPSC)-derived neural progenitor cells (NPCs) to increase expression of α9 integrinwithin the developing rat CST. We demonstrate that human NPCs (hNPCs) express endogenous levels of both α9 and β1 integrin subunits as well as cortical neuron markers such as chicken ovalbumin upstream promoter transcription factor (COUP-TF) interacting protein 2 (Ctip2) and T-box brain 1 (Tbr1). In addition, lentivirus-mediated α9 integrin overexpression in hNPCs resulted in increased neurite outgrowth in the presence of TN-C in vitro. Following transplantation into the sensorimotor cortex of newborn rats, both wild type (WT) and α9-expressing hNPCs extend along the endogenous CST and retain expression of α9 throughout the length of the axonal compartment for up to 8 weeks following transplantation. These data highlight the growth potential of transplanted human iPSCs which may be a future target for regenerative therapies after nervous system injury.